2017
DOI: 10.1016/j.rbmo.2016.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreserved embryo transfer: adjacent or non-adjacent to failed fresh long GnRH-agonist protocol IVF cycle

Abstract: The optimal time to perform cryopreserved embryo transfer (CET) after a failed oocyte retrieval-embryo transfer (OR-ET) cycle is unknown. Similar clinical pregnancy rates were recently reported in immediate and delayed CET, performed after failed fresh OR-ET, in cycles with the gonadotrophin-releasing hormone (GnRH) antagonist protocol. This study compared outcomes of CET performed adjacently (<50 days, n = 67) and non-adjacently (≥50 to 120 days, n = 62) to the last OR-day of cycles with the GnRH agonist down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 36 publications
(37 reference statements)
1
46
2
Order By: Relevance
“…However, those studies included only FET cycles following ovarian stimulation with GnRH antagonist cycles, and this conclusion should not be assumed as valid surrogates for the potential carryover effect of COS on pregnancy outcomes following GnRH agonist protocol. To this extent, another research team found significantly higher live birth rate in the non-adjacent group than in the adjacent group (32.3% versus 13.4%,P = 0.01), and support the postponement of FET after a failed fresh transfer when a preceding long GnRH-agonist protocol was used [12]. The literatures mentioned above on the optimal FET timing were paradoxical due to the different COS protocol.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…However, those studies included only FET cycles following ovarian stimulation with GnRH antagonist cycles, and this conclusion should not be assumed as valid surrogates for the potential carryover effect of COS on pregnancy outcomes following GnRH agonist protocol. To this extent, another research team found significantly higher live birth rate in the non-adjacent group than in the adjacent group (32.3% versus 13.4%,P = 0.01), and support the postponement of FET after a failed fresh transfer when a preceding long GnRH-agonist protocol was used [12]. The literatures mentioned above on the optimal FET timing were paradoxical due to the different COS protocol.…”
Section: Discussionmentioning
confidence: 76%
“…And there's no strong evidence to support the practice. Only a few studies were designed to explore different time interval between oocytes retrieval and a subsequent FET cycle on pregnancy outcomes, and the conclusions are indefinite and controversial [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…With increasing FETs, the timing of transfer after the stimulated cycle has become controversial. Prior studies have evaluated the duration of time between stimulation and frozenthawed embryo transfer [8][9][10], but only three specifically after GnRHa trigger [11][12][13]. All three showed equivalent pregnancy rates despite timing differences.…”
Section: Introductionmentioning
confidence: 99%
“…Postponement of FET would increase the anxiety of patients [10]; in the immediate FET cycle, poor endometrial receptivity or physical condition may not be fully recovered to the pre-stimulation state, which may affect pregnancy outcomes [11]. It is not clear whether the detrimental effects on endometrial receptivity caused by COH could sustain over a long period of time, up to the subsequent menstrual cycle, especially in patients with HOR who are most affected by COH.…”
Section: Introductionmentioning
confidence: 99%